079 Unmasking of motor neuron disease by botulinum toxin therapy. Issue 6 (27th May 2022) - Paluri, Srinivasa; Hassan, Muha; Lambert, Tom
Abstract : A 75 year-old male with a history of a right hemiparesis due to past h/o stroke sustained a T3 vertebral body compression fracture after a fall and was treated conservatively. Six months later, in a rehabilita- tion clinic he reported that following discharge there had been a gradual deterioration in his mobility and strength, particularly on the right side. His right upper limb had become more stiff and painful with decreased range of movements. Two months later he received Dysport injections to the right elbow flexors, right brachioradialis, soleus and right flexor carpi radialis. Four days later, he developed worsening right sided weakness, slurred quiet speech, head drop and difficulty swallowing and this persisted. On review in neurology clinic there was a head drop with neck extensor weakness, spasticity and severe weakness in his right upper and lower limbs. There were also upper and lower motor neuron signs in his left upper and lower limbs. Neurophysiology studies eventually revealed fasciculation potentials and active den- ervation changes in the left upper and lower limb raising 'the strong suspicion of generalized anterior horn cell disease'. He continued to progress and eventually passed away with pneumonia a year after the original fall. We believe this is a case of incipient motor neuron disease unmasked by botulinum toxin treatment. This is not a recognized phenomenon though it has previously been reported. s.paluri@nhs.net